Effect of Diabetes Exercise on Depression Score in Type II Diabetes Mellitus Patients - Romadhani Tri Purnomo; Puput Risti Kusumaningrum; Fitriana Noor Khayati; H Harjana (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Diabetes mellitus is a chronic disease that occurs when the pancreas is unable to produce enough insulin. Indonesia is the 7th most DM sufferer in the world. Patients when diagnosed with DM experience psychological stress, anxiety because they are no longer like normal people, causing depression. The way to reduce depression is to do physical activity such as gymnastics. The purpose of this study was to determine the effect of diabetic exercise on the reduction of depression scores at Persadia RSI Klaten. This study used a quasy experimental pre post test design with a cross sectional approach. The study population was type II DM patients who joined Persadia Islamic Hospital Klaten. The sampling technique was purposive sampling with a total of 30 respondents. The data collection instrument used the PHQ questionnaire. Bivariate data analysis using the Wilcoxon test. The results of the research on the characteristics of respondents were dominated by women as many as 23 (76.7%). The average age of the respondents was 49 years. The ethnic group is dominated by Javanese as many as 28 (93.3%). Most of the respondents' occupation is Labor 12 (40.0%). The average score for depression before the intervention for diabetic exercise was 7,400 and after the intervention for diabetic exercise decreased to 2.166. The results of the Wilcoxon test showed that there was a significant effect of diabetes exercise on the reduction of depression scores in type II diabetes mellitus patients at Persadia RSI Klaten values ??(p = 0.000, Z = -4.813). Conclusion based on the results of the study, the average depression score in Type II DM patients before diabetes exercise was 7,400. Meanwhile, the average depression score after diabetes exercise was 2.166. The results of statistical tests showed that there was an effect of diabetes exercise on depression scores in Type II DM patients with a p value of 0.000.